The Timelessness of Augustine’s Didactic Thought - Marek, Zbigniew; Walulik, Anna (Paedagogia Christiana, 2017)
The catechetical work De catechizandis rudibus, that is, The initial teaching of religion, due to the way Saint Augustine treats its addressee and the addressees of his preaching, can be considered valid for successive generations of educators – not just catechists or teachers. The whole process of catechetical instruction which is the subject of Augustine’s insightful study is essential for understanding education in a broader sense – as humanistic education, which should not be reduced to the technological aspect, but should be considered in terms of the overall impact of the mutual relationship between the teacher and the student. Augustine’s reflections pertain to the foundations of educational processes that are implied by the concept of man as a bodily and spiritual being, to his world of values, and to the connection between catechetical teaching and everyday human life. By appreciating the existential dimension of catechesis Augustine contributes to the reflection on the possibility of natural and religious cognition in search of the meaning and purpose of life. In this way he shows the specificity of Christian humanism and the opportunities it offers in solving educational problems. The methodology proposed by St. Augustine sensitizes us to the educational aspect of didactics. It shows that the separation of didactic and educational influences is contrary to the idea of integral human development, which is inherent to the personalist pedagogy. It entails the conviction that every teacher, regardless of his field of specialization, is an educator.